B1 and B2 kinin receptor blockade improves psoriasis‐like disease. (30th May 2020) - Soley, Bruna da Silva; Silva, Leonardo Martins; Mendes, Daniel Augusto Gasparin Bueno; Báfica, André; Pesquero, João Bosco; Bader, Michael; Witherden, Deborah A.; Havran, Wendy L.; Calixto, João B.; Otuki, Michel Fleith; Cabrini, Daniela Almeida
Abstract : Background and Purpose: The entire kallikrein–kinin system is present in the skin, and it is thought to exert a relevant role in cutaneous diseases, including psoriasis. The present study was designed to evaluate the relevance of kinin receptors in the development and progression of a model of psoriasis in mice. Experimental Approach: The effects of kinin B1 and B2 receptor knockout and of kinin receptor antagonists (SSR240612C or FR173657) were assessed in a model of psoriasis induced by imiquimod in C57BL/6 mice. Severity of psoriasis was assessed by histological and immunohistochemical assays of skin, along with objective scores based on the clinical psoriasis area and severity index. Key Results: Both kinin receptors were up‐regulated following 6 days of imiquimod treatment. Kinin B1 and B2 receptor deficiency and the use of selective antagonists show morphological and histological improvement of the psoriasis hallmarks. This protective effect was associated with a decrease in undifferentiated and proliferating keratinocytes, decreased cellularity (neutrophils, macrophages, and CD4 + T lymphocytes), reduced γδ T cells, and lower accumulation of IL‐17. The lack of B2 receptors resulted in reduced CD8 + T cells in the psoriatic skin. Relevantly, blocking kinin receptors reflected the improvement of psoriasis disease in the well‐being behaviour of the mice. Conclusions and Implications: Kinins exerted critical roles in imiquimod‐induced psoriasis. Both B1 and B2 kinin receptors exacerbated the disease, influencing keratinocyte proliferation and immunopathology. Antagonists of one or even both kinin receptors might constitute a new strategy for the clinical treatment of psoriasis.